Structure of soil Collembola communities as bioindicators in conservation areas of West Lombok, West Nusa Tenggara, Indonesia - IMMY SUCI ROHYANI; AHMAD JUPRI; ISROWATI ISROWATI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rohyani IS, Jupri A, Isrowati. 2025. Structure of soil Collembola communities as bioindicators in conservation areas of West Lombok, West Nusa Tenggara, Indonesia. Biodiversitas 26: 4374-4383. Conservation areas maintain the diversity of plants, animals, types of ecosystems, and natural uniqueness, as well as the protection of soil, water, climate, and historical and cultural values within them. One effort to maintain the function of conservation areas is improving soil fertility by maximizing the role of soil organisms, one of which is soil Collembola. This research aims to analyze the community structure of Collembola and utilize its potential as a bioindicator of soil conditions in four conservation areas in West Lombok District, West Nusa Tenggara Province, Indonesia. The research locations include Karandangan Nature Tourism Park, Suranadi Nature Tourism Park, and Nuraksa Forest Park in the Protection Block and Utilization Block. The approach used is quantitative descriptive-exploratory. Samples were taken purposively using pitfall traps, chicken bait traps, and soil sampling, then extracted with a Berlese funnel. Community structure was analyzed using diversity indices, species richness, dominance, and evenness. The potential of bioindicators was assessed based on the relationship between the abundance of the Collembola genus and soil environmental parameters (organic C, total nitrogen, moisture, water content, available phosphorus and Cation Exchange Capacity/CEC). The results showed a stable community structure, with high genus richness and evenness, moderate diversity, and low dominance. The genera Isotomiella, Pseudosinella, and Callyntrura have the potential to be used as bioindicators of low organic carbon, total nitrogen, soil moisture, and water content. The genera Mimoderus, Proisotoma, Pseudachorutes, Oudemansia, and Pseudoparonella have the potential to be used as bioindicators of low phosphorus availability and soil cation exchange capacity. This finding suggests the potential of Collembola as an effective bioindicator for monitoring soil quality in sustainable conservation area management.